The dark side of business model innovation: An empirical investigation into the evolvement of customer resistance and the effectiveness of potential countermeasures - Sven Heidenreich; Elena Freisinger; Christian Landau (Journal of Product Innovation Management, 2022)
In the past decade, a core assumption of research on business model innovation (BMI) has been its beneficial character. However, studies have shown that potentially disrupting BMI is not immune to failure. Still, studies that investigate the causes of BMI failures are lacking. This article shifts the focus to the dark side of BMI by using a demand-side approach, which cross-fertilizes on the new product development (NPD) research stream of passive innovation resistance. We argue that BMI, like any other type of innovation, imposes change on the customer, which endangers the status quo. As a result, passive innovation resistance evolves, potentially disrupting continuous adoption. Thus, the main goal of the current study is to investigate whether and how BMI evokes negative effects of passive innovation resistance on customers' adoption behavior (Study 1) and to determine which marketing instruments can be used as countermeasures (Study 2). Our findings confirm that passive innovation resistance is a strong inhibitor of continuous BMI adoption. However, the detrimental effects of passive innovation resistance on continuous BMI adoption can be attenuated by employing benefit comparisons or testimonials in business model (BM) announcements. From a theoretical perspective, this study enhances the current knowledge on how stable customer predispositions affect the adoption process of BMI. By so doing, our study confirms the applicability of passive innovation resistance beyond the NPD domain but also sheds light on differences in the cause-effect mechanism between BMI and product innovation contexts. From a managerial perspective, this study equips managers with effective countermeasures to passive innovation resistance that should reduce the probability of BMI failure.
Keywords: 650; business model innovation; customer adoption; customer resistance; marketing instruments; passive innovation resistance